Efektivitas Kebijakan Kedaulatan Pangan di Indonesia - Muslih, M (Wajah Hukum, 2024)
The food sovereignty policy as regulated in the Food Law is intended to support the fulfillment of food security, with requirements for the utilization of local resource potential. In its development, food security is met, however, the use of local resource potential is inferior to the use of imported food, even reaching half of the need for the staple food rice. . This reality must be taken seriously by all parties, because if it is allowed to continue, it will be detrimental to society, even the State of Indonesia, because of the high level of dependence on foreign food. It is necessary to develop legal awareness among the public, government officials and all elements of the nation. Indicators of legal awareness include knowledge of norms, understanding the purpose of norms and willingness to implement norms. For this reason, education, outreach, affirmative action, supervision and role modeling by community/government figures are highly expected. The research method used in this paper is a sociological legal research method, because the object of the research is not legal norms (Food Law), but rather the implementation of the commands of these norms. To obtain data as an object of study and analysis, the data is obtained from direct observations in the field and published observations of other parties which are relevant to the object of study in this paper. The discussion is that the reality of wheat imports reaching 11.33 million tonnes per year is comparable to half (½) of the national rice requirement. This can be interpreted to mean that even though national food security and sufficiency has been achieved, if we look at Article 42 of the Food Law, food sovereignty has not been successful. For this reason, the government and all elements of society must be aware and move together to develop legal awareness of the negative impacts of our dependence on foreign commodities.